Comparison of sporulation and germination conditions for Clostridium perfringens type A and G strains - Liggins, Marc; Ramírez Ramírez, Norma; Abel-Santos, Ernesto (Frontiers in Microbiology, 2023)
Clostridium perfringens is a spore forming, anaerobic, Gram-positive bacterium that causes a range of diseases in humans and animals. C. perfringens forms spores, structures that are derived from the vegetative cell under conditions of nutrient deprivation and that allows survival under harsh environmental conditions. To return to vegetative growth, C. perfringens spores must germinate when conditions are favorable. Previous work in analyzing C. perfringens spore germination has produced strain-specific results. Hence, we analyzed the requirements for spore formation and germination in seven different C. perfringens strains. Our data showed that C. perfringens sporulation conditions are strain-specific, but germination responses are homogenous in all strains tested. C. perfringens spores can germinate using two distinct pathways. The first germination pathway (the amino acid-only pathway or AA) requires L-alanine, L-phenylalanine, and sodium ions (Na+) as co-germinants. L-arginine is not a required germinant but potentiates germination. The AA pathway is inhibited by aromatic amino acids and potassium ions (K+). Bicarbonate (HCO3-), on the other hand, bypasses potassium-mediated inhibition of C. perfringens spore germination through the AA pathway. The second germination pathway (the bile salt / amino acid pathway or BA) is more promiscuous and is activated by several bile salts and amino acids. In contrast to the AA pathway, the BA pathway is insensitive to Na+, although it can be activated by either K+ or HCO3-. We hypothesize that some C. perfringens strains may have evolved these two distinct germination pathways to ensure spore response to different host environments.